Effects of fish oil hepatic peroxidation in rats andantioxidant role of vitamin E - Naime CANORUÇ; Nihat GÜRKAN; Nuriye METE; Aydın KETANİ and Fikri CANORUÇ (Turkish Journal of Gastroenterology, 2019)
-